Antillonatus, a new replacement name for the generic homonym Antillopsyche Núñez & Davis, 2016 (Lepidoptera: Tineoidea: Psychidae) - Aguila, Rayner Núñez; Davis, Don R. (Zootaxa, 2016)
We have been informed that the name Antillopsyche Núñez & Davis 2016, type species Antillopsyche sessilis Núñez & Davis, 2016, which we recently proposed for a new genus of bagworm moths (Núñez & Davis 2016), is preoccupied by Antillopsyche Banks, 1941. This senior name was published for a genus of Trichoptera in the family Polycentropodidae (Banks 1941). We therefore propose the new name Antillonatus Núñez & Davis to replace the junior homonym Antillopsyche Núñez & Davis. The new generic name is derived from Antillae, the Latin word for Antilles, the archipelago where this taxon occurs, and the Latin natus (be born/begotten/arisen) in reference to the West Indian origin of the type species, which is the only known member of the genus.